Role of Public Relations in a Company - Flowerina, Indria; Syaidah, Shalma (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
Companies today are growing and developing extremely normally, developing an increasingly diverse audience, both external and internal, requiring special treatment when communicating with them. Corporate communications activities are strategic communications that must be implemented according to the company. This comic activity involves management as a key decision-maker in the company. Through strategic communication, the company's PR can run well. PR needs to get full management support to complete the task, the purpose of this research is to describe the pent role that PR does in a company. The method used in this research is a library study that connects research with existing literature and fills gaps in previous research. The research results obtained on this research are some of the roles of a PR in a company.